The Association Between the Baseline and the Change in Neutrophil-to-Lymphocyte Ratio and Short-Term Mortality in Patients With Acute Respiratory Distress Syndrome - Zhang, Wei; Wang, Yadan; Li, Weijie; Wang, Guizuo (Frontiers in Medicine, 2021)
Background: Two previous studies have shown that increased neutrophil to lymphocyte ratio (NLR) is associated with short-term prognosis in patients with acute respiratory distress syndrome (ARDS), but it is usually assessed as a single threshold value at baseline. We investigated the relationship between the baseline and the early change in NLR and 30-day mortality in patients with ARDS to evaluate the prognostic value of NLR baseline and of NLR changes during the first 7 days after ICU admission. Methods: This is a retrospective cohort study, with all ARDS patients diagnosed according to the Berlin definition from the Medical Information Mart for Intensive Care III (MIMIC-III) database. We calculated the NLR by dividing the neutrophil count by the lymphocyte count. The multivariable logistic regression analysis was used to investigate the relationship between the baseline NLR and short-term mortality. Then the generalized additive mixed model was used to compare trends in NLR over time among survivors and non-survivors after adjusting for potential confounders. Results: A total of 1164 patients were enrolled in our study. Multivariable logistic regression analysis showed that after adjusting for confounders, elevated baseline NLR was a significant risk factor predicting 30-day mortality (OR 1.02, 95%CI 1.01, 1.03, P = 0.0046) and hospital mortality (OR 1.02, 95%CI 1.01, 1.03, P = 0.0003). The result of the generalized additive mixed model showed that the NLR decreased in the survival group and increased in the non-survival group gradually within 7 day after ICU admission. The difference between the two groups showed a trend of increase gradually and the difference increased by an average of 0.67 daily after adjusting for confounders. Conclusions: We confirmed that there was a positive correlation between baseline NLR and short-term mortality, and we found significant differences in NLR changes over time between non-survival group and survival group. The early increase in NLR was associated with short-term mortality in ARDS patients.